The Palaikastro Kouros and Iconoclasm in the Wider Mediterranean Area. (8th November 2022) - Whittaker, Helene
Abstract : This article discusses the chryselephantine statue known as the Palaikastro Kouros, which was recovered in the excavations at Palaikastro in eastern Crete in the 1980s. The statue and the sanctuary building in which it had stood had been deliberately destroyed c. 1450 bc . It is probable that the motivation for the destruction was iconoclastic. This situates the fate of the Palaikastro Kouros within a broader context of iconoclasm in the ancient Near East and Mediterranean area.